Facile Preparation of Cu‐Al Oxide Catalysts and Their Application in the Direct Synthesis of Ethanol from Syngas. Issue 32 (13th November 2017) - Li, Xiaoli; Zhang, Qingde; Xie, Hongjuan; Gao, Xiaofeng; Wu, Yingquan; Yang, Guohui; Wang, Peng; Tian, Shaopeng; Tan, Yisheng
Abstract: A simplified catalytic system K‐Cu/Al2 O3 (KCA‐xCu‐ T ) with Cu‐Al oxides was prepared by a facile impregnation method and was successfully applied in the direct synthesis of ethanol from syngas. The results demonstrated that the distribution of CuO, CuAl2 O4, and CuAlO2 in KCA‐xCu‐ T catalysts can be effectively tuned by varying the calcination temperature ( T /°C) and CuO loading (xCu/wt%). The cooperative effect between Cu 0 and CuAlO2 (Cu + ) was proved to be responsible for the enhanced ethanol selectivity. Furthermore, the formation of CuAlO2 could efficiently fix Cu + species in KCA‐10Cu‐900 sample, and thus lead to excellent catalytic stability (300 h at 400 °C). CuAl2 O4 itself has no catalytic effect but can be gradually decomposed into Cu + and/or Cu 0 species during reaction, which further influenced the ethanol selectivity (38.4 wt%). Abstract : The distribution of CuO, CuAlO2, and CuAl2 O4 strongly depended on calcination temperature and CuO loading. The balancing effect between Cu 0 and CuAlO2 (Cu + ) was demonstrated to be responsible for the formation of ethanol and CuAl2 O4 has no catalytic effect. Whta's more, KCA‐10Cu‐900 sample showed the high ethanol selectivity (38.4 wt%) and excellent catalytic stability (300 h at 400 °C ) due to the formation of CuAlO2 .